Wanprestasi Sewa Menyewa Sawah Dengan Sistem Bayar Musim Panen - Zulfan Efendi Hasibuan, Irpah Yanti Tanjung & (Jurnal El-Thawalib, 2021)
This research discusses of wanprestasi in renting rice field with a harvestseason payment system in Bottot Village, Sorkam District, Central TapanuliRegency. This research is motivated due to the element of wanprestasi made bythe people who entered into the lease agreement. The results showed that theimplementation of the pillar and conditions for renting rice field with the harvestseason payment system was in accordance with the Compilation of IslamicEconomic Law. However, the implementation of responsibilities in paying wages /rice field rental fees is not in accordance with the Compilation of IslamicEconomic Law. because in practice, the fulfillment of the payment of the rice fieldrental occurs in wanprestasi or in broken This promises. The factor in theoccurrence of the default was that the rice field rental agreement was carried outverbally and without witnesses being present. Apart from that, the lack of theprinciple of responsibility and honesty on the part of the party that is in default isalso one of the factors. Based on the description above, what must be done is toapply a written agreement and be attended by witnesses if you want to make arental agreement for renting the fields, and be wiser in responding to fraudcommitted by parties who wanprestasi.